Impact of advanced imaging techniques on preoperative planning in cardiac surgery. Issue 12 (2nd September 2022) - Cotton, Jake; Groves, Daniel W.; Vargas, Daniel; Morrison, Justin; Desai, Aken; Rove, Jessica Y.
Abstract: Background and Aim of the Study : Review how advanced imaging techniques and a multidisciplinary heart team approach are used to evaluate complex cardiac structural pathology. Methods : Single‐center retrospective case series. Results and Conclusions : Cardiac computed tomography angiography in addition to transthoracic and transesophageal echocardiography impacts pre‐procedural planning and procedural success.